Anthropology, Development and Interculturalism: Proposals from Latin America - Cortés Maisonave, Almudena (Revista de Antropología Social, 2014)
This text that introduces the monograph presents the contributions that social anthropology has made in the analysis of development and interculturalism from Latin America. The interest of this work is twofold. On the one hand, Latin America has been a privileged geopolitical laboratory where programs and projects were fostered and exported to other parts of the world. Moreover, the contributions made by Latin American anthropology have been important milestones in the study of development and interculturalism. Without being exhaustive, the articles included in this special issue give a good account of it, and focus on debates around development, the role of ODA and NGOs in Latin America, or for example, the consequences of interculturalism and ethnic development proposals made in the region.